Sonic the Hedgehog. The fate of Dr. Eggman. Part 1 - Flynn, Ian, 1982- (Spotlight, 2020)
Espio the Chameleon and the Chaotix call on Sonic the Hedgehog with a surprise he never expected--Dr. Eggman has been found, but he has no memory of his past life. Now calling himself Mr. Tinker, Eggman has been helping the villagers repair their equipment and make their lives better. Yet someone sinister is still acting behind the scenes.